Comparative study of polycyclic aromatic hydrocarbons (PAHs) and heavy metals (HMs) in corals, surrounding sediments and surface water at the Dazhou Island, China. (March 2019) - Yang, Tinghan; Cheng, Huamin; Wang, Haihua; Drews, Marco; Li, Sennan; Huang, Wei; Zhou, Hailong; Chen, Chien Min; Diao, Xiaoping
Abstract: This study investigated polycyclic aromatic hydrocarbons (PAHs) content in corals ( Acropora sp. ), surficial sediments, and surface seawater, and heavy metals (HMs) contents in corals and sediments from Dazhou Island, Hainan, China. Concentrations of PAHs in seawater and sediment seasonally ranged from 191.5 ng L −1 to 587.7 ng L −1, and from 37.9 ng g −1 to 233 ng g −1, while levels in corals were higher (185.2–545.0 ng g −1 ) compared to those found in sediments, demonstrating bioaccumulation of PAHs by corals. A similar seasonally variation of PAHs was observed in water/sediments and corals, and the proportions of low molecular weight PAHs (LPAHs) in seawater and corals were higher. Pyrolytic and petrogenic contaminations were identified to be the main sources of PAHs. Lower HMs concentrations were detected in corals (9.8–39.4 μg g −1 ) than in sediments (65.0–83.3 μg g −1 ), but HMs bioaccumulation still occurs in corals. Higher concentrations of HMs in sediment and corals were detected in March and December, especially Mn and Zn. Application of an enrichment factor showed that Cu in corals was delivered from non-crustal materials, and anthropogenic inputs were possibly the main sources. According to Biota Sediment Accumulation Factor, corals could strongly bioaccumulate LPAHs and Cd, and PAHs at a higher ( p < 0.05) rate than HMs. There was a lack of correlation between the accumulation of PAHs and HMs in corals based on the cluster analysis. Dual hierarchical clustering analysis result revealed that feeding, instead of symbiosis, might be the main process responsible for the bioaccumulation of PAHs and HMs. Highlights: The seasonal variations of PAHs and HMs in corals, surrounding sediments and surface water were reported. There were the linear correlations between PAHs concentrations in corals and sediments, and in corals and seawater. PAHs were bioaccumulated in a higher rate than HMs in corals. Feeding, instead of symbiosis, may be the main process responsible for the bioaccumulation of PAHs and HMs. Corals are useful bioindicator species of PAHs and HMs in coral reef monitoring.